The impact of foreign direct investment from Western Europe to East Asia. - Chatonda Mhone Slade. (2008)
As the world goes on to experience the globalization phenomenon, Foreign Direct Investment (FDI) has become a crucial part of growth and development. FDI has created and consolidated trade flows so much that countries have become interdependent for goods and services on the one hand and for capital on the other. This study attempts to evaluate the role that FDI from Western Europe has played in the growth process of East Asian nations. Comparative analyses on Singapore, Thailand, and Taiwan were undertaken in order to assess the impact of FDI from Western Europe. This study, therefore, is an attempt to examine the interaction between FDI activity and economic growth in these host nations. It analyzes and makes an evaluation of the nature of the relationship between FDI activities and economic structures of the host nations and, it then looks into the trend of productivity growth of these host countries as a result of FDI activities. The study also provides background on theory and evidence about the impact of FDI on development as a basis for decision making. It brings out the implications that might arise for developing countries about to embark upon policies to attract FDI.